Follicular helper T cells (Tfh): heterogeneity in spatial distribution and phenotypic characteristics - Shen, Caifeng; Fu, Qiong (Frontiers in Immunology, 2025)
Follicular helper T cells (Tfh) are a Th cell subset that directly assists B cells in functioning, and their development is regulated by various factors. Among them, the initial regulation leads to phenotypic heterogeneity, while the regulation of their migration process results in spatial heterogeneity. The phenotypic heterogeneity is manifested by the presence of Tfh subsets with characteristics helper T cells (Th) of other lineages, namely Tfh1, Tfh2, and Tfh17, with different transcriptional programs and secrete distinct cytokines, potentially possessing different functions. The spatial heterogeneity is mainly manifested by the positional relationship between Tfh and germinal centers (GC), which are mainly divided into GC-Tfh, follicular mantle Tfh, and circulating Tfh, possibly reflecting the process of Tfh occurrence. This review summarizes the spatial and phenotypic heterogeneity of Tfh cells, and suggests a Tfh cell type framework with nodes of previous studied cell types and the edges of switching between specific celltypes, which is affected by the summation of imprinted plasticity part and de novo plasticity part in Tfh development, connecting the hypothesis Crotty et al. proposed in 2018. Discrete cell type is still eligible in qualifying the diseases state and quantifying the activity and severity of diseases, but it could also be beneficial to look Tfh from the view of cell states and expression programs, which, in the future studies, might better model the through process of Tfh development and unifying the contradiction caused by separate Tfh cell type view.